Growth of the native cladocero Ceriodaphnia sp with chlorophytes (Scenedesmus sp and Chlorella sp) under laboratory conditions - Ismiño Orbe, Rosa Angélica (2020)
The effect of the chlorophytes Scenedesmus sp and Chlorella sp used as feed on the growth of the native cladoceran Ceriodaphnia sp were studied. Three treatments with three repetitions for each chlorophyte were used: T1 = 5 ml.L-1 (25 x 106 cells), T2 = 10 ml.L-1 (50 x 106 cells) and T3 = 15 ml.L-1 (75 x 106 cel). The physical and chemical characteristics of the water in the containers varied between 28.4 and 28.6 °C, pH between 6.57 and 7.36 and the dissolved oxygen between 6.34 and 6.66 mg/l between treatments. The results showed that Ceriodaphnia sp prefers the Chlorella sp microalgae, where diets with a concentration of 10 ml.l-1 (50 x 106 cells) were better than the other diets.